Students’ Perspectives Towards English Academic Competence Test (TKA) - Roobby Hamdanur (English Language Education, Universitas Internasional Batam, 2026)
This study focuses on examining students’ perceptions of the English Academic Competence Test (TKA). The study employed a quantitative descriptive design involving 40 high school students in Medan, Indonesia, who were selected using purposive sampling. Data were collected using a Likert-scale questionnaire consisting of 20 items and covering five dimensions: general perception, level of difficulty and comprehension, test-taking experience, impact on learning, and obstacles and expectations. The instrument validation results indicated that 15 items were deemed valid, and the instrument demonstrated high reliability (Cronbach’s Alpha = 0.861). Descriptive statistical analysis indicates that students generally have a positive perception of the English TKA, with an overall mean score of 3.03. The “impact on learning” dimension received the highest mean score (M = 3.23), suggesting that students view the TKA as beneficial in helping identify weaknesses and supporting improvements in English proficiency. However, students still face difficulties in vocabulary mastery, reading comprehension, and questions requiring higher-order thinking skills (HOTS). These findings imply the need to strengthen literacy, enrich vocabulary, and develop critical thinking skills in English language learning to improve students’ readiness for academic assessments.